Strapping rowers to their sliding seat improves performance during the start of single-scull rowing - van Soest, A. J.; de Koning, H.; Hofmijster, M. J. (Journal of Sports Sciences, 2016)
In this study, the effect of strapping rowers to their sliding seat on performance during 75 m on-water starting trials was investigated. Well-trained rowers performed 75 m maximum-effort starts using an instrumented single scull equipped with a redesigned sliding seat system, both under normal conditions and while strapped to the sliding seat. Strapping rowers to their sliding seat resulted in a 0.45 s lead after 75 m, corresponding to an increase in average boat velocity of about 2.5%. Corresponding effect sizes were large. No significant changes were observed in general stroke cycle characteristics. No indications of additional boat heaving and pitching under strapped conditions were found. The increase in boat velocity is estimated to correspond to an increase in average mechanical power output during the start of on-water rowing between 5% and 10%, which is substantial but smaller than the 12% increase found in a previous study on ergometer starting. We conclude that, after a very short period of adaptation to the strapped condition, single-scull starting performance is substantially improved when the rower is strapped to the sliding seat.